Floating Exchange Rates in Developing Countries : Experience with Auction and Interbank Markets - Huh, Kyong (Occasional Papers; Occasional Paper, 1987)
In recent years, an increasing number of developing countries have adopted market-determined floating exchange rates. This development has represented a significant step forward in the evolution toward exchange rate flexibility that has taken place in the developing country group since the adoption of generalized floating by industrial countries in 1973.